The Impact of ESG Score on Company Value in Southeast Asia: The Role of Competitive Advantage as a Moderating Variable - Yolanda Joshua; Dony Abdul Chalid (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) scores on firm value in Southeast Asia, with a focus on how competitive advantage influences this relationship. Using panel data from 90 publicly listed companies across five ASEAN countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) from 2018 to 2023, the research applies fixed-effects regression models to analyze the data. Tobin’s Q is used as a proxy for firm value, while ESG scores are obtained from Refinitiv. Competitive advantage is measured using operational efficiency indicators.The results show that higher ESG scores have a negative effect on firm value, which contradicts the common belief that ESG practices improve corporate valuation. This suggests that ESG implementation may impose additional costs or operational constraints, especially in emerging markets where regulations and awareness are still developing. However, competitive advantage plays a moderating role in this relationship. Firms with strong competitive positions are better able to manage ESG-related risks and costs, helping to reduce the negative impact on firm value. These findings highlight the importance of aligning ESG strategies with a company's core strengths to ensure sustainability efforts do not harm financial performance. Investors should consider both ESG performance and competitive positioning when making decisions. Policymakers are encouraged to design ESG regulations that support sustainability without negatively affecting firm valuation. This study contributes to the growing literature on ESG performance in emerging markets and offers practical insights for firms, investors, and regulators in Southeast Asia. Future research can explore other moderating factors such as industry type, macroeconomic conditions, and regulatory environments.